(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Focal hepatic lesions comprise a wide spectrum of benign and malignant pathologies, requiring accurate imaging-based differentiation for appropriate clinical management. Triple-phase Multidetector Computed Tomography (MDCT) plays a vital role in lesion characterization by evaluating dynamic enhancement patterns during different vascular phases. Aim & Objectives: To evaluate the diagnostic efficacy of triple-phase MDCT in the characterization and differentiation of focal hepatic lesions and to correlate imaging findings with histopathological examination. Materials & Methods: This prospective cross-sectional study was conducted over 12 months in the Department of Radiodiagnosis, Rajah Muthiah Medical College and Hospital. Fifty patients aged >20 years with suspected or ultrasonographically detected focal liver lesions underwent triple-phase MDCT. Lesions were assessed for morphology, enhancement patterns, vascular involvement, and extrahepatic features. Histopathology (FNAC, biopsy, or surgical specimens) served as the reference standard where available. Results: Among the 50 patients studied, benign lesions constituted 68% of cases, while malignant lesions accounted for 32%. Hepatic abscess was the most common benign lesion (36%), whereas metastasis was the most common malignant lesion (18%). Hemangiomas demonstrated characteristic peripheral nodular enhancement with centripetal fill-in, while hepatocellular carcinoma showed arterial hyperenhancement with portal venous washout. Triple-phase MDCT correctly characterized 43 out of 44 histopathologically correlated cases, yielding an overall diagnostic accuracy of 97.5%. Additional findings such as portal vein thrombosis, inflammatory hyperemia, and metastatic spread were effectively demonstrated. Conclusion: Triple-phase MDCT is a highly sensitive, rapid, and reliable imaging modality for evaluating focal hepatic lesions. Characteristic enhancement patterns enable accurate differentiation of benign & malignant lesions and provide essential information for diagnosis, staging, and treatment planning.